Do Farmers Choose to Be Inefficient? Evidence from Bicol, Philippines - Larson, Donald F.; Plessmann, Frank (World Bank, Washington, DC, 2013)
Farming households that differ in their ability, or willingness to take on risks are likely to make different decisions when allocating resources, and effort among income-producing activities, with consequences for productivity. The authors measure voluntary, and involuntary departures from efficiency for rice-producing households in Bicol, Philippines. They take advantage of a panel of household observations from 1978, 1983, and 1994. The unusually long-time span of the panel provides ample opportunities for the surveyed households to learn, and apply successful available technologies. The authors find evidence that diversification, and technology choices do effect outcomes among farmers, although these effects are not dominant. Accumulated wealth, past decisions to invest in education, favorable market conditions, and propitious weather are also important determinants of efficiency outcomes among Bicol rice farmers.